A MULTI AGENT DECISION TREE ALGORITHM FOR SUPPLY CHAIN MANAGEMENT (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
The issue of interest here is the behavior of decision agents in supply chain management. The study uses a managerial framework to organize supply-related tasks to the behavior of specific instantiations of decision agents. The reasons why organizations might elect to invest supply chain management responsibilities in decision agents rather than humanÂ functionaries are illustrated. Finally, this research presents a final construct for optimal agent-based decision making opportunities. The implication is that a shift of power from humans to computers is shown to be quite effective on technically tractable decision situations.